Problematical Aspects of the Suspension of the Execution of an Arrest Punishment in Lithuania - Švedas, Gintaras; Levon, Justyna (Teisė, 2022)
This article analyzes the aspects of the reasonableness of the new institute of suspension of the execution of an arrest punishment in the Republic of Lithuania. It identifies possible problematic aspects of the application of this institute and the ways to solve them.
Keywords: arrest; suspension of the punishment execution; reasonableness